Advances in the Study of Acne in Adult Women - Wang, Bi; Yan, Xiaoning (Journal of Contemporary Medical Practice, 2024)
The clinical presentation of acne in adult women is different from that of adolescent acne, with a more complex pathogenesis, and treatment along the lines of standard acne treatments is ineffective. Due to the chronicity of the disease course and the involvement of facial lesions, acne has been shown to have a serious negative impact on the quality of life of adult female patients. In this article, we review the clinical manifestations, etiology and pathogenesis, and treatment of acne in adult females in light of the recent advances in acne research in China and abroad, intending to provide a reference for further research on the disease.